1972
DOI: 10.1113/jphysiol.1972.sp009757
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of sodium transport in barnacle muscle fibres by means of the microsyringe technique

Abstract: SUMMARY1. The cation composition of single barnacle muscle fibres following damage by axial insertion of a microsyringe has been measured. The Na and Ca contents of these fibres were raised.2. Electronmicroscopic studies of fibres following insertion of a microsyringe indicated that the damage done resulted in tubular obstruction of the T-system.3. Fibres loaded with radiosodium by micro-injection showed that the Na* efflux declined exponentially with time, but that in most fibres the Injections of distilled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1977
1977
1982
1982

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Earlier work showed that exposure of barnacle muscle fibers (isolated from Monterey Bay specimens) to 30 mM K stimulates the Na efflux in ouabain-treated and untreated fibers (Danielson et al, 1971;Bittar et al, 1972). This work has been confirmed (Bittar et al, 1973).…”
Section: Stimulation By Raised External K Of the Ouabain-insensitive supporting
confidence: 76%
See 1 more Smart Citation
“…Earlier work showed that exposure of barnacle muscle fibers (isolated from Monterey Bay specimens) to 30 mM K stimulates the Na efflux in ouabain-treated and untreated fibers (Danielson et al, 1971;Bittar et al, 1972). This work has been confirmed (Bittar et al, 1973).…”
Section: Stimulation By Raised External K Of the Ouabain-insensitive supporting
confidence: 76%
“…Bittar et al (1972) reported that the Na efflux in fibers isolated from Monterey Bay The effect of Na+-free ASW on the response of the ouabain-insensitive Na efflux to 100 mM K. (B): The effect of varying external Na § on the response of the ouabain-insensitive Na efflux to 100 mM K. The ordinate is the average maximum rate constant for the stimulated Na &flux relative to that measured separately in control experiments using normal (100%) Na § The number of observations made at each concentration tested is indicated in parenthesis. Vertical bars indicate • sE~ specimens is stimulated even when external Ca z + is removed.…”
Section: Dependence On External Cations Of the Response To Raised K (mentioning
confidence: 97%
“…However, it must also be noted that ai a did not rise significantly in any of the fibres and so possibly the interfibre spaces were still not completely K-free even though, in the experiment shown, the fibre was superfused with 0 KO for over 50 min, causing a hyperpolarization of the membrane potential of over 20 mV. Nevertheless, experiments on the Na pump in Maia and giant barnacle fibres, using radiotracers and Na-loaded muscles have indicated that 0 Ko can halve Na-pumping into normal Ringer within 10-20 min 249 R. D. VA UGHAN-JONES (Bittar, Caldwell & Lowe, 1967;Brinley, 1968;Bittar, Chen, Danielson, Hartmann & Tong, 1972 In two other experiments, treatment with 2 x 104 M ouabain for about an hour caused aNa to rise by about 2 and 1 m-mole/hr, and in the fourth experiment 10-5M ouabain caused no rise whatsoever of apla over a 40 min period. In all experiments there was no substantial reduction in the response to low Nao.…”
mentioning
confidence: 99%
“…Single muscle fibres were isolated by dissection from the depressor muscle bundles and cannulated, as previously described (Bittar, Chen, Danielson, Hartmann & Tong, 1972). The fibres used were 3-5 cm in length and 1-2 mm in width.…”
Section: Methodsmentioning
confidence: 99%